The Effectiveness of Diet Menu Schedule Education on Knowledge and Blood Glucose Levels Among Patients with Diabetes Mellitus at Sultan Iskandar Muda Hospital, Nagan Raya, in 2026 - Yusridawati Yusridawati; Widyawati Widyawati; Nurhaida Nurhaida; Riny Apriani; Syahfira Ananda Syahna (Benih : Journal of Midwifery, 2026)
Type 2 diabetes mellitus is a chronic disease requiring comprehensive management, including proper dietary regulation. Poor adherence to meal schedules often results in uncontrolled blood glucose levels despite patients' awareness of recommended food choices. Diet menu schedule education is considered an important non-pharmacological intervention to improve patients' knowledge and glycemic control. This study aimed to determine the effectiveness of diet menu schedule education on patients' knowledge and blood glucose levels among individuals with diabetes mellitus at Sultan Iskandar Muda Hospital, Nagan Raya, Indonesia. A quantitative study employing a quasi-experimental one-group pretest-posttest design was conducted involving 30 patients with type 2 diabetes mellitus selected through purposive sampling. Participants received structured diet menu schedule education. Knowledge was assessed using a validated questionnaire, while random blood glucose levels were measured through clinical examination. Data were analyzed using the Paired Sample t-test with a significance level of 0.05. Before the intervention, most participants demonstrated poor knowledge (63.3%), with a mean blood glucose level of 236.4 mg/dL. Following the educational intervention, 76.6% of participants achieved good knowledge scores, while the mean blood glucose level significantly decreased to 149.1 mg/dL. Statistical analysis revealed significant improvements in both knowledge and blood glucose levels after the intervention (p < 0.001). Diet menu schedule education effectively improved patients' knowledge and significantly reduced blood glucose levels among individuals with type 2 diabetes mellitus. This educational strategy should be incorporated into routine diabetes management programs to enhance patients' self-management and glycemic control.